Involvement of Ca2+-ATPase in suppressing the appearance of bovine helically motile spermatozoa with intense force prior to cryopreservation - DURITAHALA; Mitsuhiro SAKASE; Hiroshi HARAYAMA (The Society for Reproduction and Development, 2022)
In cattle, cryopreserved spermatozoa are generally used for artificial insemination (AI). Many of these specimens exhibit helical movement, although the molecular mechanisms underlying this phenomenon remain unclear. This study aimed to characterize helically motile spermatozoa, investigate the involvement of Ca2+-ATPase in suppressing the appearance of these spermatozoa prior to cryopreservation, and examine the potential of helical movement as an index of sperm quality. In the cryopreserved semen, approximately 50% of spermatozoa were helically motile, whereas approximately 25% were planarly motile. The helically motile samples swam significantly faster than those with planar movement, in both non-viscous medium and viscous medium containing polyvinylpyrrolidone. In contrast, in non-cryopreserved semen, planarly motile spermatozoa outnumbered those that were helically motile. Fluorescence microscopy with Fluo-3/AM and propidium iodide showed that flagellar [Ca2+]i was significantly higher in cryopreserved live spermatozoa than in non-cryopreserved live ones. The percentage of non-cryopreserved helically motile spermatozoa was approximately 25% after washing, and this increased significantly to approximately 50% after treatment with an inhibitor of sarcoplasmic reticulum Ca2+-ATPases (SERCAs), "thapsigargin." Immunostaining showed the presence of SERCAs in sperm necks. Additionally, the percentages of cryopreserved helically motile spermatozoa showed large inter-bull differences and a significantly positive correlation with post-AI conception rates, indicating that helical movement has the potential to serve as a predictor of the fertilizing ability of these spermatozoa. These results suggest that SERCAs in the neck suppress the cytoplasmic Ca2+-dependent appearance of helically motile spermatozoa with intense force in semen prior to cryopreservation.